Midnight Street Scene - Hegg, Eric A., 1867-1948 (Manuscripts, Archives, and Special Collections, Washington State University Libraries: https://libraries.wsu.edu/masc, 1898)
1 Photographic Print: b&w; 25 x 20.5 cm. Title from photograph. 2326.